Litotripsia extracorpórea (2007)
Generalidades/Historia/Propiedades físicas de las ondas de choque/Mecanismo para desintegrar las piedras/Efectos biológicos/Las posibles complicaciones o efectos secundarios de la Lec/Contraindicaciones e indicaciones/Secuencia del tratamiento/Cuidado postratamiento/Corolario.